Effect of Dietary Supplementation of Different Levels of Zinc on Feed Intake, Growth Performance, Carcass Characteristics and Physical Quality of Meat in Sheep : 10.5958/2581-6616.2020.00015.8 - Reddy, P. Baswa; Ramana, D.B.V.; Naveena, B.M.; Sen, A.R. (Journal of Meat Science, 2020)
An experiment was conducted in Deccani ram lambs to study the effect of supplementing different levels of zinc (Zn) in the diet on growth performance, feed intake, carcass characteristics and meat quality. Twenty-four weaned native Deccani ram lambs weighing around 12-15 kg were divided into four groups of six each. They were fed with adlib finely chopped maize straw and concentrate feed @ 1% of body weight for 120 days. Concentrate feed offered to different groups differed in the zinc content which was supplemented in the form of ZnSO4.7H2O. Group 1 was used as negative control where no mineral mixture was added in the concentrate mixture. In Group 2 (control), mineral mixture was used @ 2%. In group 3 and 4, in addition to mineral mixture, ZnSO4.7H2O was added @ 70g and 140g per 100 kg concentrate mixture respectively. Feed intake and body weights of animals were recorded during the entire experimental period. After the feeding trial, animals were slaughtered to study the carcass characteristics and meat quality parameters. The results indicated that additional zinc supplementation did not show any effect (P>0.05) on feed intake or body weight gain between groups. Carcass characteristics were also similar (P>0.05) between the groups There was significant (P
Keywords: Feed; Meat quality; Sheep; Zinc